ADMINISTRASI DAN SUPERVISI PENDIDIKAN ISLAM KURIKULUM BERBASIS CINTA PENGEMBANGAN MATARI AJAR PADA SEKOLAH DASAR - Adinda Trikano; Juairiah Juairiah; Ahmad Zainuri; Frika Fatimah Zahra (JIP: Jurnal Ilmu Pendidikan, 2025)
This study examines the administration and supervision of Islamic education in developing teaching materials based on a love curriculum in elementary schools. The love-based curriculum places the value of compassion as the foundation of learning to shape students with intellectual, emotional, and spiritual intelligence. The research method used a descriptive qualitative approach with primary data from interviews, observations, and documentation. Findings indicate that the implementation of this curriculum improves discipline, learning motivation, and harmonious relationships among students. Supervision is carried out collaboratively and humanistically to support teacher professionalism in integrating the value of love into the learning process. Evaluation also assesses students' affective and socio-emotional aspects. Key challenges include teacher readiness, school culture, and the national evaluation system. This study concludes that the love-based curriculum is effective in building Islamic and social character in elementary education, but requires comprehensive guidance and support.